2020
DOI: 10.1111/jcmm.14942
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LINC00467 drives hepatocellular carcinoma progression via inhibiting NR4A3

Abstract: Hepatocellular carcinoma (HCC) is a main cause of cancer‐related deaths globally. Long non‐coding RNAs (lncRNAs) play important roles in diverse cancers. Our previous microarray‐based lncRNA profiling showed that LINC00467 was highly expressed in HCC. Here, we further explored the expression, role and functional mechanism of lncRNA LINC00467 in HCC. Our findings revealed that LINC00467 was up‐regulated in HCC tissues and HCC cell lines. Increased expression of LINC00467 was positively associated with tumour si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…NR4A3 embraces different characterize of biological functions upon specific pathogenesis of diseases. [33][34][35][36][37] Based on the two mRNA datasets, NR4A3 is up-regulated in PAH samples, consistent with our findings. In vivo experiment, we found that NR4A3 was up-regulated in MCT-PAH rat model tissues and in vitro experiment.…”
Section: Discussionsupporting
confidence: 87%
“…NR4A3 embraces different characterize of biological functions upon specific pathogenesis of diseases. [33][34][35][36][37] Based on the two mRNA datasets, NR4A3 is up-regulated in PAH samples, consistent with our findings. In vivo experiment, we found that NR4A3 was up-regulated in MCT-PAH rat model tissues and in vitro experiment.…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting that studies on HCC have shown that LINC00467 expression is higher in HCC tissues than in controls ( Jiang et al, 2020 ; Wang et al, 2020 ; Zheng et al, 2020 ) However, Cai et al (2019 ) reported the opposite result in their clinical samples. Furthermore, they found that LINC00467 expression in HCC tissues with metastasis was lower than that in non-metastatic tissues.…”
Section: Discussionmentioning
confidence: 92%
“…( Jiang et al, 2020 ) In addition, LINC00467 can post-transcriptionally reduce the expression of the tumor suppressor NR4A3 by regulating Dicer-dependent RNA splicing, which ultimately contributes to HCC tumorigenesis. ( Wang et al, 2020 )…”
Section: Molecular Mechanism Of Linc00467 In Diverse Human Cancersmentioning
confidence: 99%
“…The aberrant expression of LINC00467 has been identified in diverse tumors like hepatocellular carcinoma, glioma, and neuroblastoma 16,34,35 . Especially, upregulated LINC00467 exhibited oncogenic roles to promote cell proliferation or prevented cell apoptosis in lung adenocarcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%